Bridging Extension Gaps through Digital Advisory Systems: Lessons from a Mobile Expert System for Rice Farmers in Nigeria (International Journal of Agricultural Extension and Education, 2025)
Agricultural extension services remain unevenly distributed across rural Nigeria,  limiting smallholder farmers’ access to timely and context-specific agronomic  knowledge. This study examines the role of mobile-based expert systems as a  socio-technical intervention for strengthening agricultural extension in resource constrained rural settings. Using a Design Science Research approach, we developed  and evaluated RiceAdvisor, a mobile expert system designed to support rice disease  diagnosis and management among smallholder farmers. System requirements were  informed by survey data collected from 270 rice farmers across three agro-ecological  zones in Nigeria, highlighting critical gaps in disease diagnosis, extension access,  and decision support. The system integrates localized expert knowledge, rule-based  reasoning, multilingual interaction, and offline functionality to accommodate  rural infrastructural and literacy constraints. Usability evaluation with 50 farmers  produced a System Usability Scale score of 76.5, indicating acceptable to good usability  and perceived relevance. Findings suggest that mobile expert systems can enhance  farmers’ confidence, problem-solving capacity, and access to extension knowledge,  particularly in contexts where conventional advisory services are limited. The study  contributes to rural studies and agricultural extension services by demonstrating  how digital advisory tools can be designed and embedded within rural knowledge  systems to support sustainable agricultural practices in Nigeria.
Keywords: Rural Livelihoods, Digital Agriculture, Rice Farming